Shyness During Foley Catheter Insertion - Suyanto, Suyanto; Amal, Ahmad Ikhlasul; Noor, Mohammad Arifin (International Journal of Psychosocial Rehabilitation, 2026)
Foley catheter insertion in patients treated in hospitals is common. This catheter placement has dif erent goals between one patient and another. Insertion that is done can provide a dif erent experience. The aim of this study was to know the ef ect of catheter placement in relation to shyness. Shyness and foley catheter were the research variables. This research used a cross-sectional method with 60 respondents has already catheter placement in first day treatment. Consecutive sampling used in this study with distribution frequency analysis with a catheter related bladder discomfort questionnaire were used to get the data in this study. This research was conducted at Sultan Agung Islamic Hospital. Frequency distribution was used for analysis in this study. The results obtained that as many as 47 respondents (76.7%) expressed shyness during insertion, and 25 respondents (41.7%) had shyness during foley catheter placement. Catheter insertion absolutely increases shyness response for most respondents, and during length of placement catheter shyness response decrease. Other research needs to be done on factors related to shyness in patients with foley catheter insertion.